Technology enabled transformation of the public sector advances in e-government - Weerakkody, Vishanth (Premier reference source, 2012)
"This book contains original research about electronic government and supplies academicians, practitioners, and professionals with quality applied research results in the field of electronic/digital government, its applications, and impacts on governmental organizations around the world" - Provided by publisher